2019
DOI: 10.1016/j.jtumed.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles and satisfaction with educational activities of Saudi Health Science University Students

Abstract: ObjectivesMedical knowledge is constantly changing; this puts pressure on educators to adapt instructional strategies to their students' learning styles (LSs). Therefore, identifying the LSs of medical students could help teachers to develop teaching strategies to achieve better outcomes. The purpose of this study was to determine the LSs of health science university students, and to assess the relationship between LSs and student satisfaction with educational activities.MethodsThis cross-sectional descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
2
14
1
2
Order By: Relevance
“…(Guraya et al, 2014). Our findings is contradictory to another study done in Saudi Arabia where the most popular learning style was Accommodator (Al Shaikh et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…(Guraya et al, 2014). Our findings is contradictory to another study done in Saudi Arabia where the most popular learning style was Accommodator (Al Shaikh et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, Wang showed that learning styles do not affect participants' satisfaction with the teaching approach [32]. The results of many studies show a weak relationship between learning styles and learning outcomes [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies using the Kolb LSI, medical students generally showed learning style characteristics similar to the current study. 12,18 Studies have shown that the most common learning styles reported in medical students are assimilating, converging and accommodating. 10,19 Moreover,…”
Section: Discussionmentioning
confidence: 99%